Students science process skills under structured and guided inquiry learning condition - Wasis Wuyung Wisnu Brata; Cicik Suriani (Universitas Ahmad Dahlan, 2020)
Inquiry learning has been known as a popular approach to be studied and applied in science learning. However, the effect of different levels of inquiry on science process skills has not received much attention. This study aims to see the effect of the implementation of guided and structured inquiry on students' Science Process Skills. The quasi-experimental method was carried out with the posttest-only control group Randomized design in two classes of Biology's first-year students. Data were collected with a process skill observation sheet for one semester of lectures. The results showed that both types of inquiry learning showed similar achievement patterns for the types of process skills observed, but generally guided inquiry showed better results. The average score of science process skills in structured inquiry classes was 71.67, while in guided inquiry classes was 78.06. Another interesting finding is that the two types of inquiry learning produce similar performance patterns for the type of process skills observed. The sequence of the type of process skills that are most mastered in both classes is to observe, conclude, classify, and communicate. Inquiry learning is able to develop science process skills well, but differences in learning experiences that are more open to guided inquiry are thought to be an explanation of the difference in achievement of process skills between the two types of inquiry.